2013
DOI: 10.1245/s10434-013-3164-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival After Adrenalectomy for Stage I/II Adrenocortical Carcinoma (ACC): A Retrospective Comparative Cohort Study of Laparoscopic Versus Open Approach

Abstract: LA was associated with a shorter length of stay and did not compromise the long-term oncological outcome of patients operated on for stage I/II ACC ≤ 10 cm ACC. Our results suggest that LA can be safely proposed to patients with potentially malignant adrenal lesions smaller than 10 cm and without evidence of extra-adrenal extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 52 publications
0
85
0
8
Order By: Relevance
“…Nine cohort studies on the surgical treatment of patients with nonmetastatic adrenocortical carcinoma were included (151,152,153,154,155,156,157,158,159). Three studies reported on the patients in whom complete resection of the tumor was achieved (153,155,159).…”
Section: Surgical Approach: Open Vs Minimally Invasive Adrenalectomy mentioning
confidence: 99%
See 1 more Smart Citation
“…Nine cohort studies on the surgical treatment of patients with nonmetastatic adrenocortical carcinoma were included (151,152,153,154,155,156,157,158,159). Three studies reported on the patients in whom complete resection of the tumor was achieved (153,155,159).…”
Section: Surgical Approach: Open Vs Minimally Invasive Adrenalectomy mentioning
confidence: 99%
“…These studies also provided data on overall or disease-specific survival (151,152,153,154,155,157,158,159). There is no compelling evidence that one of the approaches (laparoscopic or open adrenalectomy) is superior with regard to time to recurrence and/or survival in patients with adrenocortical carcinoma, provided that rupture of tumor capsule is excluded.…”
Section: Recurrence-free and Overall Survivalmentioning
confidence: 99%
“…Traditionally, if ACC was recognized intraoperatively, conversion to an open procedure was mandated, since the laparoscopic approach had been linked to increased local recurrence, tumor seeding at port sites, and peritoneal spread. A recent study, however, has shown no diference in long-term oncological outcomes in carefully selected patients with stage I/II ACC, tumors <10 cm, and no evidence of extra-adrenal invasion, who underwent laparoscopic adrenalectomy by experienced surgeons [18].…”
Section: Adrenocortical Carcinomamentioning
confidence: 96%
“…In literature there are many publications comparing both methods and their complications, radical oncological therapy, duration of the operation, blood loss, and hospitalisation time. In most cases, the laparoscopic method seems to be better than the open procedure [7,8]. The surgical technique must be adjusted to the patients' needs.…”
Section: Introductionmentioning
confidence: 99%